Energy transfer aspects of chemically reactive Casson fluid between a conical gap of cone-disk system with multiple rotations - M. Qamar; M. Khan; A.S. Alqahtani; M.Y. Malik (Results in Engineering)
Casson fluids have been widely used in engineering and biotechnology including, energy systems, polymer fluids, pharmaceuticals, chocolate, automotive industries, blood, and honey. In view of such useful applications, the current study examines the thermal properties of a steady Casson fluid flow squeezing within a permeable cone-disk object depending on Ohmic dissipation, activation energy, variable thermal conductivity, magnetic field, non-uniform heat source/sink, and thermal radiation. Three different models are analyzed including; (i) rotating cone and disk (ii) rotating cone stationary disk (iii) rotating disk and stationary cone. The physical characteristics of nonlinear PDEs are converted into nonlinear coupled ODEs utilizing the right similarity variables. These transformed non-dimensionless equations are resolved utilizing the bvp4c Lobatto IIIA technique via Matlab software. The influence of physical factors like velocity, temperature, concentration, drag friction, heat transportation rate, and Sherwood number are explored theoretically and graphically. We have found that radial velocity profile across three models improved with an increment in the Casson fluid factor. It is noted that the thermal distribution profile is boosted as the thermal conductivity parameter increases resulting in a strong thermal effect within the flow field. Furthermore, the mass profile shows upsurge behavior with an enhancement in activation energy factor. Additionally, the magnetic field parameter shows an increasing trend for drag friction, while a reverse trend can be observed for heat transportation rate. This work is 99.5 % compatible with the published article for radiation factor values 1.0,2.0,3.0. It observed in all considered models of cone-disk apparatus the best cooling was achieved for the stationary cone and rotating disk. The cone-disk apparatus contributes valuable insights into industrial and engineering fields including refining air compression, pharmaceutical processes, gas turbines to improve cooling efficiency systems, medical uses, inkjet printing, automatic and spinning systems.